The causal associations between growth factors and constipation: a two-sample Mendelian randomization study - Wang, Jiachen; Yang, Mingyi; Xu, Ke; Wan, Xianjie; Xie, Jiale; Yu, Hui; Fang, Jiaxin; Wang, Zehua; Xu, Peng (Frontiers in Physiology, 2023)
Abstract: Introduction: Certain growth factors (GFs) are associated with constipation, but no study has analyzed the causal associations between the two. Therefore, this study used two-sample Mendelian randomization to systematically analyze the causal associations between GFs levels and constipation based on genome-wide association studies (GWAS) data. Methods: Both GF and constipation data were obtained from European populations. GFs as an exposure variable was obtained from a genetic map of the human plasma proteome containing 3,301 samples, another GWAS dataset on 90 circulating proteins containing 30,931 samples, and a GWAS dataset containing 3788 samples. Constipation as an outcome variable was obtained from FinnGen project containing 26,919 cases and 282,235 controls and another UK Biobank dataset containing 3,328 cases and 459,682 controls. Single nucleotide polymorphisms strongly associated with GFs were regarded as instrumental variables. Inverse variance weighting, MR-Egger regression, weight median, simple mode, and weight mode methods were used to determine genetic associations. The Cochrane Q test, Egger-intercept, and MR-PRESSO were used to analyze sensitivity. Results: The IVW analysis based on FinnGen showed that NGFI-A binding protein 2 and vascular endothelial growth factor receptor 2 were inversely associated with constipation, and fibroblast growth factor 7 and transforming growth factor beta receptor II levels were positively associated with constipation. The IVW analysis based on UK Biobank showed that proheparin-binding epidermal growth factor, platelet-derived growth factor AA, and vascular endothelial growth factor121 were inversely associated with constipation. Conclusion: This study showed that some GFs are genetically associated with the risk of constipation.